Hybrid Organizations in Health Systems: The Corporatization of Malaysia's National Heart Institute. Issue 1 (1st December 2020) - Virk, Amrit; Croke, Kevin; Mohd Yusoff, Mariana; Mokhtaruddin, Khairiah; Abdullah, Zalilah; Nadziha Mohd Hanafiah, Ainul; Soleha Ramli, Emira; Filzatun Borhan, Nor; Almodovar Diaz, Yadira; Aun, Yap Wei; Atun, Rifat
ABSTRACT: Health system reforms across high- and middle-income countries often involve changes to public hospital governance. Corporatization is one such reform, in which public sector hospitals are granted greater functional independence while remaining publicly owned. In theory, this can improve public hospital efficiency, while retaining a public service ethos. However, the extent to which efficiency gains are realized and public purpose is maintained depends on policy choices about governance and payment systems. We present a case study of Malaysia's National Heart Institute (IJN), which was created in 1992 by corporatization of one department in a large public hospital. The aim of the paper is to examine whether IJN has achieved the goals for which it was created, and if so, whether it provides a potential model for further reforms in Malaysia and other similar health systems. Using a combination of document analysis and key informant interviews, we examine key governance, health financing and payment, and equity issues. For governance, we highlight the choice to have IJN owned by and answerable to a Ministry of Finance (MOF) holding company and MOF-appointed board, rather than the Ministry of Health (MOH). On financing and payment, we analyze the implications of IJN's combined role as fee-for-service provider to MOH as well as provider of care to private patients. For equity, we analyze the targeting of IJN care across publicly-referred and private patients. These issues demonstrate unresolved tensions between IJN's objectives and public service goals. As an institutional innovation that has endured for 28 years and grown dramatically in size and revenue, IJN's trajectory offers critical insights on the relevance of the hybrid public-private models for hospitals in Malaysia as well as in other middle-income countries. While IJN appears to have achieved its goal of establishing itself as a commercially viable, publicly owned center of clinical excellence in Malaysia, the value for money and equity of the services it provides to the Ministry of Health remain unclear. IJN is accountable to a small Ministry of Finance holding company, which means that detailed information required to evaluate these critical questions is not published. The case of IJN highlights that corporatization cannot achieve its stated goals of efficiency, innovation, and equity in isolation; rather it must be supported by broader reforms, including of health financing, payment, governance, and transparency, in order to ensure that autonomous hospitals improve quality and provide efficient care in an equitable way.